The Inventory System of Hi-Cool Industrial Corporation - Acedillo, Theresa T. (College of Engineering, 1995)
HI-COOL ENGINEERING CORPORATION which was founded in 1978 is an organization concerned with the design, supply, installation and service of Air-conditioning systems. It presently imports equipment from Japan, Korea, Taiwan and Italy. In as much as there is a lead time of 2 to 3 months when importing equipment from abroad, the company maintains a certain stock level to be able to meet demand expectations. However, customer may opt to wait if there is no available stock on hand. The role of an accurate inventory or stock report is thus important as orders from the suppliers abroad are dependent on what is on hand and the sales expectations from the coming months. This decision is made by the president of the company which, by the way, makes several other decisions even in the operational level. Apparently, decisions are highly centralized. An accounting clerk is in charge of generating the monthly stock report of all imported equipments. Inventories of local materials which are used in installation are not maintained as these are readily available from local suppliers. The scope of the study will cover the inventory system of the company under study as this area is observed to present a lot of opportunities for improvement. For instance, the stock report is estimated to be only 85% accurate as information flow between accounting and the different warehouses is weak and discontinuous. The existing standard operating procedures are not strictly followed by the warehouse people and are at times overruled by the decision of the CEO. Inventory tracking is presently handled by one person in the accounting department, which is only one among his other duties.